Inovasi Metode Pembelajaran Fakultas Ushuluddin UIN Sunan Kalijaga: Menjembatani Tradisi dan Modernitas - Renata, Tiara; Syaefudin, Syaefudin (Paedagogie, 2025)
This study discusses the innovation of learning methods at the Faculty of Ushuluddin, UIN Sunan Kalijaga, with a focus on efforts to preserve traditional learning methods amidst educational modernization. In the digital era, educational institutions face the challenge of remaining relevant without neglecting traditional values, which are an important part of the identity of Islamic education. In this context, it is important to explore how the faculty integrates technology and innovation while maintaining classical learning methods. The purpose of this study is to analyze the Faculty of Ushuluddin's strategy in preserving traditional learning methods, identify the faculty's role in developing Islamic education innovation, and reveal students' and lecturers' perceptions of the implementation of hybrid education. This study is expected to provide theoretical contributions to the development of Islamic education and become a practical reference for the faculty in formulating learning strategies that harmonize tradition and innovation. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The study was conducted at the Faculty of Ushuluddin, involving several students as sources. Data analysis was carried out descriptively and interpretively, using the Miles and Huberman analysis model, which includes data reduction, data presentation, and conclusion drawing.